Metformin/glibenclamide-related interstitial lung disease: a case report - Zuccarini, Giacomo; Bocchino, Marialuisa; Assante, Luca Rosario; Rea, Gaetano; Sanduzzi, Alessandro (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Interstitial lung disease (ILD) may be caused by a wide panel of recognized drugs. Despite the increasing number of reports in the literature, high-lightings of ILD related to oral hypoglycemic drugs are very infrequent.  Herein, we describe the case of a 78-yr-old Caucasian diabetic woman who developed mild dyspnoea at rest, asthenia and fever while on treatment with oral metformin (2000 mg/day) and glibenclamide (12.5 mg/day). On hospital admission, pulmonary function testing (PFT), chest x-ray and thorax high resolution computed tomography (HRCT) were consistent with a diagnosis of ILD. The patient’s clinical conditions significantly improved soon after the initiation of insulin therapy instead of oral anti-diabetics due to poor glycemic control. After excluding other known etiologies, the significant improvement in PFT along with the complete resolution of the radiologic findings in the absence of any additional therapeutic effort at 3 months suggested the causal link between previous oral hypoglycemic therapy and lung toxicity. Clinicians should always consider the role of drugs as causative agent in the diagnostic work-up of patients with suspected ILD. To our knowledge, this is the second report in the literature of a case of ILD related to the treatment with high doses of anti-diabetic drugs in a poorly controlled diabetic woman.